Financing of public sports and leisure policies by Ceará municipalities - Edmilson Santos dos Santos; Maria José Carvalho (Universidade Salgado de Oliveira, 2021)
This descriptive and exploratory study has aimed to assess the participation of municipalities from Ceará in the financing of sport and leisure public policies through a unit analysis of expenditure in the Sport and Leisure Function (SLF). The period of analysis refers to the ten first years during which information has been made available on the Brazilian Public Sector Accounting and Fiscal Information System, from the National Treasure Department, from 2002 to 2011. Municipalities from Ceará don't prefer inaction and present high adhesion to the sport and leisure agenda. Results of CP4 and TU3 indicate a strong expansion on expenditures in higher levels of urbanization and population class. Throughout the period, expenses in SLF have increased in a quite significant manner.